A Pilot Study with Randomised Controlled Design Comparing TiZr Alloy Dental Implants to Ti Implants - Kristina Hultin; Annelie Eriksson; Christina Backe; Ulf Johansson; Kostas Bougas (eJournal of Oral Maxillofacial Research)
Objectives: Evidence on the clinical performance of recently introduced dental implants in titanium-zirconium alloy is sparse. The aim of the present pilot study with randomized controlled design is to compare changes in supporting structures around dental titanium-zirconium alloy implants to commercially pure titanium implants.